IMPROVING LIBRARY SERVICES IN HIGH SCHOOLS - Try Julian Ditya; Wahira; Hasan (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to find out how library services are and what are the supporting and inhibiting factors for library services at SMA Negeri 1 Soppeng. This research uses a qualitative approach, therefore in order to achieve a research objective, data collection methods are used, namely interviews, observations and documentation. The data sources in this study are school principals, library heads, library staff, teachers and students at SMA Negeri 1 Soppeng. The data analysis of this study is data reduction, data presentation and conclusion drawn. The results of this study show that library services at SMA Negeri 1 Soppeng consist of technical services and user/user services. Technical services carried out at SMA Negeri 1 Soppeng include procurement, inventory, classification and cataloging which are services provided by the library to make it easier for users to access the collection. User/user services at SMA Negeri 1 Soppeng consist of circulation services and reference services which are services to help users and provide information to users. The supporting factors for library services at SMA Negeri 1 Soppeng are library officer services, the availability of technology, facilities, and an easy borrowing and return system. The factors that hinder the library service of SMA Negeri 1 Soppeng are the physical condition of the building which is not spacious, the availability of books that need to be added such as non-fiction books and lesson package books as well as facilities such as computers that sometimes cannot be used.